The Oxford Handbook of Deliberative Democracy 2018
DOI: 10.1093/oxfordhb/9780198747369.013.32
|View full text |Cite
|
Sign up to set email alerts
|

Deliberation and Equality

Abstract: Political systems are democratic to the extent that people are empowered to participate in political practices—such as voting, representing, deliberating, and resisting—that contribute to self-and collective-rule. There is a close relationship between equality and democracy, as equality distributes symmetrical empowerments that enable people affected by collective endeavors to participate in political practices that contribute to self- and collective-rule. This chapter elucidates the relationship between equal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…This form of inclusion naturally supports deliberative quality and thus also addresses deliberative deficits. There is now ample evidence that deliberative mini-publics do, in fact, achieve high-quality deliberation Warren & Gastil 2015;Cutler et al 2008;Warren & Pearse 2008;Beauvais & Bächtiger 2016;Knobloch & Gastil 2015;Smith 2009;Beauvais 2018). While we will not reiterate this evidence, we will underscore those design features incorporated into the GWCA that likely supported high-quality learning and deliberation.…”
Section: Using Deliberative Mini-publics To Address Democratic Deficitsmentioning
confidence: 87%
“…This form of inclusion naturally supports deliberative quality and thus also addresses deliberative deficits. There is now ample evidence that deliberative mini-publics do, in fact, achieve high-quality deliberation Warren & Gastil 2015;Cutler et al 2008;Warren & Pearse 2008;Beauvais & Bächtiger 2016;Knobloch & Gastil 2015;Smith 2009;Beauvais 2018). While we will not reiterate this evidence, we will underscore those design features incorporated into the GWCA that likely supported high-quality learning and deliberation.…”
Section: Using Deliberative Mini-publics To Address Democratic Deficitsmentioning
confidence: 87%
“…For instance, Beauvais (2018), Beauvais and Bächtiger (2016) and Young (2011) have suggested that the abstract ideal of universal moral equality underlying the 'first generation' ideal of rational deliberation should be complemented with more situated ideals of equity and justice. The latter are rooted in the recognition of the significant differences between different social groups in their access to wealth and power as well as their physical, cognitive and linguistic styles and abilities (Beauvais 2018). The later representatives of the deliberative tradition have thus adjusted the deliberative ideal by making it more sensitive to the pluralist aspirations and dimensions of modern democracies (Bächtiger et al 2018).…”
Section: A Defence Of Deliberative Democracy and Democratic Educationmentioning
confidence: 99%
“…Instead, along with the pursuit of reasoned consensus or compromise, actual deliberative processes are governed by different personal and collective interests, relations of power and various systemic and structural features (Dryzek 2000;Young 2000). Especially in formal democratic institutions, systematic distortions in deliberation easily create hierarchical and oppressive structures that prevent historically disempowered group members from using their political rights or influencing deliberative processes (Beauvais 2018). This, in turn, might indeed result in the construction of such inegalitarian institutions and orders that Biesta warns against.…”
Section: A Defence Of Deliberative Democracy and Democratic Educationmentioning
confidence: 99%
“…Democratic theorists, including deliberative democrats, consider political equality as one of the normative bases of deliberative democracy (see Swift 2006: 209-213;Dahl 1998;Beauvais 2018). Realizing the ideal of political equality is manifest in the design of minipublics through random selection and the equal consideration of participants' preferences (Fishkin 2009: 43, 54-55).…”
Section: Self-government As the Normative Criterion And Criticism Of mentioning
confidence: 99%